Navigating psychosocial challenges: An analysis of Ariel's self-development in Sayonara no asa ni yakusoku no hana wo kazarou by Mari Okada - Isnayani, Ulfa Mutiara; Widyatwati, Ken; Suryadi, Muhammad (Japanese Research on Linguistics, Literature, and Culture, 2024)
This research aimed to explain the narrative structures and stages of self-development of Ariel from the anime Sayonara no Asa ni Yakusoku no Hana wo Kazarou. The researcher used a psychological approach to analyze the problems that arise. Narrative theory was used to analyze the narrative aspects of the anime, while psychosocial theory was employed to examine the self-development stages of the character Ariel. This research is a literature study. The analysis explained that there are narrative elements, such as story and plot, narrative connections with space, narrative connections with time, and limitations of story information. The researcher discovered that Ariel successfully navigated the eight stages of self-development based on Erikson’s theory. The analysis concluded that Ariel reached the integrity stage of self-development because he successfully went through all stages with positive results and reached the integration stage of psychosocial and overcame all his obstacles.